Analisis Hubungan Efektivitas Program Health Tourism Terhadap Kepuasan Pasien di RS X Tahun 2024 : Analysis of the Relationship between the Effectiveness of Health Tourism Programs and Patient Satisfaction at Hospital X in 2024 - Lesmana, Muhammad Yusuf; Sobar Darmadja; Cici Demiyati (Journal of Public Health Education, 2025)
Introduction: Health tourism has become a crucial strategy for hospitals to enhance competitiveness and attract both local and international patients. RS Premier Bintaro has been designated as a health tourism provider. Currently, several services are already in place to support the health tourism program. Objectives: This study aims to examine the impact of the effectiveness of the health tourism program on patient satisfaction at RS Premier Bintaro in 2024. Method: This research employs a quantitative approach with a descriptive and analytical study design. Data collection was conducted through questionnaires distributed to patients and analyzed using SPSS. Result: The health tourism program at RS Premier Bintaro has proven effective in enhancing patient satisfaction. The patient shuttle service significantly impacted satisfaction, the room upgrade service improved patient comfort, and customer service assistance played a crucial role in shaping inpatient experiences. Meanwhile, the free teleconsultation service received positive responses from most patients, although its effect was not as strong as the other services. Conclution: The implementation of the health tourism program at RS Premier Bintaro has successfully improved patient satisfaction. Continuous education and promotion of health tourism services should be enhanced through collaboration with relevant departments.